Rawa migration to the Malay peninsula in the 19th century: the case of Pahang, Perak, and Selangor - Fathil, Fauziah; Wan Sulong, Wan Suhana; Abdul Manaf, Nor Faridah (International Institute of Islamic Thought and Civilization (ISTAC), 2018)
Little research attention has been paid to the Rawa or Rao community from West Sumatra who migrated to the Malay Peninsula. The few available accounts are scattered and fragmentary, and contradictory in some respects. The issue is complicated by the deliberate attempts of early Rawa migrants to hide their true identity, leaving their descendants in the dark as to their roots and ancestry. Several reasons may explain this disposition, one being the involvement of the Rawa people in different wars in Sumatra and the Malay Peninsula which consequently led them to be viewed by some quarters as an unruly and warlike people. This paper aims to examine the contributory reasons for the migration of Rawas to the Malay Peninsula in the 19th century focusing on the Malay States of Pahang, Perak, and Selangor, where the largest Rawa communities emerged. Using mainly qualitative, archival research, this paper highlights the impacts of Rawa migration, especially in the socio-economic and political contexts of the respective Malay States. It is also worth studying the perceptions or reactions of the British and local authorities towards the Rawas, as these too might have influenced their way of dealing with the issue of identity in relation to other groups in the Peninsula.